Joint processing of V-bearing steelmaking slag and V-bearing black shale for vanadium and iron separation - Wu, Liushun; Dai, Chao; Yan, Baijun; Wang, Haichuan; Qi, Cunjun (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
To recycle vanadium from V-bearing steelmaking slag and V-bearing black shale, the both were jointly roasted to generate vanadium-rich phase, and then vanadium was separated by magnetic separation in this study. The compositions of samples were determined by X-ray fluorescence meter and the phases in the samples were characterized using X-ray diffractometer. Experimental results showed that, with increasing the ratio of CaO content to SiO2 content in the samples, the vanadium separation efficiency first decreased, increased, and then decreased again. With increasing roasting temperature from 1423 to 1623 K, the vanadium separation efficiency increased. With increasing roasting time from one hour to four hours, the vanadium separation efficiency increased. The optimum conditions for vanadium recycling are the basicity of 1.2, roasting temperature of 1623 K, and roasting time of 4 hours. Under this condition, separation efficiency of vanadium reaches 71.6%, and the concentrate contains 3.67% V2O5 and 46.9% Fe2O3. A flow for joint processing of V-bearing steelmaking slag and V-bearing black shale was proposed, which involves vanadium separating, and tailings utilizing.